Семіотика та семантика візуальної мови народного мистецтва - Станкевич, М. (Інститут народознавства НАН України, 2007)
Represented common the conception about semiotics and semantics of folk art, thanks to work Ch. Peirce, Ch. Mores, F. Saussure. Artworks consist of logical the chains of tradition: “sign – image – text – work – metasign”. Symbols divided on group: 1) universal, 2) sacral, 3) surroundings, 4) ritual, 5) sculpturepainting.